Toxicity of Methanolic Seed Extract of Barringtonia asiatica L. (Kurz) (Lecythidaceae) from Different Place in Indonesia Against Spodotera litura F (Lepidoptera: Noctuidae) - Danar Dono; Irpan Permana (CROPSAVER, 2018)
One of the potential plants to be developed as insecticide is Barringtonia asiatica (Lecythidaceae). Phytochemicals of the same species plant is different in different place and time. This research was conducted to determine toxicity methanolic seed extract of Barringtonia asiatica from different field in Java i.e. Pangandaran, Sindangkerta, Bandung, Jatinangor, and Yogyakarta against Spodoptera litura. The evaluation of toxicity was carried out using feeding method. The result indicated that seed extract of B. asiatica showed value of toxicity from higher to lower were extract of B.asiatica from Pangandaran, Jatinangor, Sindangkerta, Bandung, and Yogyakarta respectively. The extract of B. asiatica showed rendement from higer to lower were extract of B.asiatica from Pangandaran (37.8%), Sindangkerta (36.1%), Yogyakarta (29.3%), Bandung (26.5%) and Jatinagor (25.8%). Methanolic seed extract of B.asiatica from Pangandaran showed the highest toxicity and rendement compared from the other place, with LC at 0.53%. In addition of toxic property, the extract of B. asiatica seed decreased of 50 leaf consumption and pupal weight and lenghtened development time of tested larvae. Keywords:  Biology, extract, toxicity, Barringtonia asiatica, Spodoptera  litura